Dark-eyed females: sexually dimorphic prespawning coloration results from sex-specific physiological response to hormone exposure in the sand goby Pomatoschistus minutus (Gobiiformes: Gobiidae). (3rd January 2022) - Olsson, Karin H; Nilsson Sköld, Helen; Merilaita, Sami; Kvarnemo, Charlotta
Abstract: The function and regulation of female nuptial colour signals are poorly understood. In fish, colour is often mediated by chromatophores, allowing for rapid and versatile signalling. Here, we examine a distinct but temporary black line around the eyes and snout ('dark eyes') displayed by female sand gobies before spawning and never observed in males. We investigate the regulatory mechanism of the display by analysing the number of melanophores in both sexes in vitro and their response to hormonal exposure. We also test the hypothesis that dark eyes serve an anti-glare function and focus the line of sight, by analysing the frequency, intensity and duration of the display in bright and dim light, with and without males present. We show that the sexes do not differ in terms of the number of melanophores, but that males and females respond in different ways to exposure to melanocyte-stimulating hormone, which has a stronger dilatory effect in females and results in a darker line. However, the darkness of the iris is not affected. Neither light levels nor the presence of potential mates affect the frequency of the dark eye display, but the display is longer lasting and more intense in the presence of smaller nest-holding males.